STRATEGI KERJASAMA SEKOLAH DENGAN DUNIA USAHA DAN DUNIA INDUSTRI (DU/DI) DALAM MENINGKATKAN KOMPETENSI LULUSAN PADA SMK NEGERI 3 BANDA ACEH - Azizah .; Murniati AR; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Strategy is an art to manage resources in order to achieve the goals effectively and efficiently. This study aimed to find out the capability of principal in establishing cooperation, including cooperation program between vocational high school (SMK) and business and industrial organization (DU/DI), mechanism of cooperation between SMK and DU/DI to improve the competence of graduates, and factors that influenced the cooperation between SMK and DU/DI. This study used qualitative approach with descriptive method. Techniques of data collection used were interview, observation, and documentation study. Subjects of this study were DU/DI, principal, vice principal for public relations, and school counselors in State SMK 3 of Banda Aceh. It was found from the results of the study that the cooperation programs between SMK and DU/DI were shown from the school’s vision and mission, the formulation of curriculum, the implementation of cooperation and the assessment report of cooperation. The mechanism of cooperation was shown from the agreement of both parties in the form of MOU in the implementation of industrial practice and other cooperation, which were guest speaker, the implementation of competency test, and other seminars. Factors that influenced the cooperation between SMK and DU/DI in improving the competence of graduates were shown from the involvement and the commitment of school personnel in formulating school’s regulation and profile. It is hoped that the principal and vice principal for public relations can foster the cooperation continuously. The cooperation that bases on the MOU should be socialized, so that both parties can exercise their rights and fulfill their obligations effectively. It is also hoped that State SMK 3 of Banda Aceh and the stakeholder can be more communicative in establishing cooperation in improving the competence of graduates of State SMKN 3 of Banda Aceh.Keywords: Strategic Relations and Cooperation Competency SMKAbstrak: strategi merupakan seni untuk mengelola sumber daya agar mampu mencapai sasaran yang dituju dengan efektif dan efesien. Tujuan penelitian ini adalah untuk mengetahui kemampuan kepala sekolah dalam menjalin hubungan kerjasama, meliputi: Program kerjasama SMK; Mekanisme kerjasama SMK dengan DU/DI untuk meningkatkan kompetensi lulusan; dan Faktor yang mempengaruhi hubungan kerjasama SMK dengan DU/DI. Melalui pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah DU/DI, kepala sekolah, waka humas, dan guru pembimbing pada SMK Negeri 3 Banda Aceh. Hasil penelitian ditemukan: Program SMK yaitu merumuskan visi dan misi sekolah, penyusunan kurikulum bersama, dan menjalin kerjasama dengan DU/DI; Mekanisme kerjasama SMK dengan DU/DI tergambar dari adanya kesepakatan kedua belah pihak  dalam bentuk MOU dalam pelaksanaan prakerin , kerjasama lain adalah guestpeaker, pelaksanaan uji kompetensi, audiensi dan seminar lainnya; dan faktor yang mempengaruhi hubungan kerjasama SMKN3 dengan DU/DI dalam meningkatkan kompetensi lulusan adalah terlihat dari adanya keterlibatan dan komitmen bersama tenaga personil sekolah dalam penyusunan regulasi dan profil sekolah. Diharapkan kepada kepala sekolah dan waka humas agar program kerjasama dengan DU/DI terus dibina secara berkesinambungan, kerjasama yang dilaksanakan dengan dasar MOU harus disosialisasikan agar kedua belah pihak dapat melaksanakan hak dan kewajibannya secara tepat guna, kepada SMKN 3 dan stakeholder agar lebih komunikatif dalam menjalin hubungan kerjasama dalam meningkatkan kompetensi lulusan pada SMKN3 Banda Aceh.Kata Kunci: Strategi Hubungan Kerjasama dan Kompetensi Lulusan SMK